(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2021)
Noise pollution has been recognized as one of the most vital environmental pollutions that affecting urban area’s quality of life. Sound levels at different points of the study area have been recorded and presented spatially by geostatistical analysis. A comparison has been made between the study area data in 2019 and that of 2021. In 2021 the noise level was significantly higher despite the Covid 19 pandemic. The comparative study showed that the noise level of the study area in 2021increased significantly. Noise level data in the sample points of the study area on Friday (holiday) were also collected and found that it was higher than that of even working days, especially in the evening. J. Asiat. Soc. Bangladesh, Sci. 47(2): 99-108, December 2021